2017
DOI: 10.1371/journal.pone.0180911
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic size and fat content in diabetes: A systematic review and meta-analysis of imaging studies

Abstract: ObjectivesImaging studies are expected to produce reliable information regarding the size and fat content of the pancreas. However, the available studies have produced inconclusive results. The aim of this study was to perform a systematic review and meta-analysis of imaging studies assessing pancreas size and fat content in patients with type 1 diabetes (T1DM) and type 2 diabetes (T2DM).MethodsMedline and Embase databases were performed. Studies evaluating pancreatic size (diameter, area or volume) and/or fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 46 publications
3
53
1
Order By: Relevance
“…The paradigm of T1D as a pure consequence of an autoimmune process has been questioned, both because of the failure to treat the disease with different immune interventions, but also when it has been found that the insulitis is neither common nor pronounced. Similar inflammatory cells are found also in exocrine pancreas, and the whole organ is decreased in size with different structural changes . Furthermore, it is found that the exocrine function decreases gradually in individuals already before they get manifest T1D, and exocrine function is decreased in many children with T1D .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The paradigm of T1D as a pure consequence of an autoimmune process has been questioned, both because of the failure to treat the disease with different immune interventions, but also when it has been found that the insulitis is neither common nor pronounced. Similar inflammatory cells are found also in exocrine pancreas, and the whole organ is decreased in size with different structural changes . Furthermore, it is found that the exocrine function decreases gradually in individuals already before they get manifest T1D, and exocrine function is decreased in many children with T1D .…”
Section: Discussionmentioning
confidence: 77%
“…In addition, studies show that pancreas often is smaller in patients who develop T1D, although the same smaller size also is seen in first‐degree relatives of patients with T1D …”
Section: Introductionmentioning
confidence: 99%
“…1 Indeed, many human studies, including those with prediabetes, have demonstrated that the concentration of FA in circulation negatively correlates with parameters of beta cell function in both adults and youths from different ethnic populations; 82-84 however, it should be noted that absence of a correlation between the two has also been reported. 87,88 Although it is not established whether pancreatic fat accumulation is sufficient for the development of beta cell dysfunction, or if reduction of pancreatic fat reverses beta cell dysfunction in humans, 89-91 local fat accumulation is a possible source of lipids that affect beta cell health in humans. Historically, lipotoxicity as a precipitating factor for beta cell failure was first proposed in a rodent model of T2D in which the accumulation of pancreatic fat precedes beta cell dysfunction.…”
Section: Review Of Clinical Studies That Connect Pancreatic Islet Expmentioning
confidence: 99%
“…Another study also showed that pancreatic volume was smaller in people with maturity‐onset diabetes of the young than in controls . In a meta‐analysis using ultrasonography, CT or MRI, pancreatic volume was reduced in people with T2D compared with healthy controls by 12.180 cm, 3 and fat content was higher in people with diabetes than in controls by 2.73% (95% CI 0.55‐4.91) …”
Section: Discussionmentioning
confidence: 95%
“…Inclusion criteria for white participants were: non-Hispanic white ethnicity; age [25][26][27][28][29][30][31][32][33][34][35] We recruited white participants first, followed by Korean participants to match age and BMI. We screened 56 white people.…”
Section: Participantsmentioning
confidence: 99%